Attachment Style and Emotional Intelligence in Individuals with Adverse Childhood Experiences - Zahrasari Lukita Dewi (Jurnal Psikologi, 2022)
This study specifically aims to see the profile of attachment style and emotional intelligence (EI) as part of personality and the correlation between them, specifically in individuals who have Adverse Childhood Experiences (ACE). By applying quantitative methods and purposive sampling techniques, this study implemented the ACE questionnaire to select participants who had ACE scores in the range 1-10 as the main characteristics of the sample from the men and women adult population. By using the Attachment Style Questionnaire (ASQ) and BarOn EQ-i, this study assessed the five domains of attachment style and the total, 5 composite scales, and 15 subscales of EI from 230 men and 250 women with an age range of 19-45 years. The Pearson correlational analysis results show that the Five Domains of Attachment scales are associated with the level of Total EI (r = -.121 - .576) and Composite EI scales in individuals who have ACE (r = -.17 - .74), except Confidence with Interpersonal and Stress Management, and Discomfort with Intrapersonal and Adaptability. These results are in line with the previous findings regarding the impact of childhood trauma on the personality of individuals in adulthood. Further research on physical and mental disorders related to childhood trauma, attachment style, and EI can be recommended to complement the results.